Microbiological purity determination of concentrated solutions of inorganic salts pharmaceutical preparation - Shtrimaitis, O; Zdoryk, O; Strilets, O; Georgiyants, V (Annals of Mechnikov’s Institute, 2020)
Results of microbiological purity research of compounding concentrated solutions during the period of their storage period (1 month) under different temperature conditions are given in the article. The tests were carried out according to requirements of the State Pharmacopoeia of Ukraine by direct two-layer sowing (national part). Experimentally there was found the absence of bacteria Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa. It is proved that all the analyzed samples of concentrated solutions meet the requirements regarding the quality of the water medicines for oral administration in accordance with the requirements of the State Pharmacopoeia of Ukraine.